Acute Limb Ischemia—Much More Than Just a Lack of Oxygen - Simon, Florian (Int J Mol Sci, 2018)
Acute ischemia of an extremity occurs in several stages, a lack of oxygen being the primary contributor of the event. Although underlying patho-mechanisms are similar, it is important to determine whether it is an acute or chronic event. Healthy tissue does not contain enlarged collaterals, which are formed in chronically malperfused tissue and can maintain a minimum supply despite occlusion. The underlying processes for enhanced collateral blood flow are sprouting vessels from pre-existing vessels (via angiogenesis) and a lumen extension of arterioles (via arteriogenesis). While disturbed flow patterns with associated local low shear stress upregulate angiogenesis promoting genes, elevated shear stress may trigger arteriogenesis due to increased blood volume. In case of an acute ischemia, especially during the reperfusion phase, fluid transfer occurs into the tissue while the vascular bed is simultaneously reduced and no longer reacts to vaso-relaxing factors such as nitric oxide. This process results in an exacerbative cycle, in which increased peripheral resistance leads to an additional lack of oxygen. This whole process is accompanied by an inundation of inflammatory cells, which amplify the inflammatory response by cytokine release. However, an extremity is an individual-specific composition of different tissues, so these processes may vary dramatically between patients. The image is more uniform when broken down to the single cell stage. Because each cell is dependent on energy produced from aerobic respiration, an event of acute hypoxia can be a life-threatening situation. Aerobic processes responsible for yielding adenosine triphosphate (ATP), such as the electron transport chain and oxidative phosphorylation in the mitochondria, suffer first, thus disrupting the integrity of cellular respiration. One consequence of this is irreparable damage of the cell membrane due to an imbalance of electrolytes. The eventual increase in net fluid influx associated with a decrease in intracellular pH is considered an end-stage event. Due to the lack of ATP, individual cell organelles can no longer sustain their activity, thus initiating the cascade pathways of apoptosis via the release of cytokines such as the BCL2 associated X protein (BAX). As ischemia may lead to direct necrosis, inflammatory processes are further aggravated. In the case of reperfusion, the flow of nascent oxygen will cause additional damage to the cell, further initiating apoptosis in additional surrounding cells. In particular, free oxygen radicals are formed, causing severe damage to cell membranes and desoxyribonucleic acid (DNA). However, the increased tissue stress caused by this process may be transient, as radical scavengers may attenuate the damage. Taking the above into final consideration, it is clearly elucidated that acute ischemia and subsequent reperfusion is a process that leads to acute tissue damage combined with end-organ loss of function, a condition that is difficult to counteract.